PENGAPLIKASIAN SUMBER-SUMBER HUKUM ISLAM YANG DIPERSELISIHKAN KEHUJJAHANNYA - Awaliyatur Rohmah; Sa'dibih, Muhammad Ahmad Fulka Sa'dibih (Tamaddun, 2021)
This article examines the implementation of disputed sources of Islamic law (al-adillah al-mukhtalaf fī ḥujjiyyatihā) within the framework of uṣūl al-fiqh, including istihsān, istishāb, shar‘u man qablana, sadd al-dharī‘ah, ‘amal ahl al-Madīnah, and qawl al-ṣaḥābī. The dynamic nature of contemporary Muslim societies often gives rise to new legal issues that are not explicitly addressed in the Qur’an and Sunnah. Consequently, Muslim jurists employ various methodological approaches to derive legal rulings while maintaining fidelity to the primary sources of Islamic law. Using a normative-juridical approach and literature review of classical and modern uṣūl al-fiqh works, this study finds that although these sources are disputed among scholars, they continue to play a significant role in responding to contemporary legal problems. Their application demonstrates the flexibility and adaptability of Islamic law without compromising its normative foundations.